EFFECTS OF APPLICATION OF INDUSTRIAL AND MUNICIPAL WASTE IN THE BLACK OAT CROP IN AN OXISOL UNDER NO-TILL - Cardoso dos Santos, Susiane de Moura; Antonangelo, Joao Arthur; Fernandes Deus, Angelica Cristina; Bull, Leonardo Theodoro (Univ Estadual Mato Grosso Sul, 2015)
The rational use of industrial and municipal waste in agriculture under no-till (NT) may promote benefits on the physical, chemical and biological properties of soil, thus reducing the use of synthetic fertilizers, providing beneficial effects to soil and ecosystem. In addition to reducing the acidity of the soil, these residues are excellent sources of nutrients for plants. The objective of this was to evaluate the nutritional status and dry matter yield of black oats after application of industrial and municipal waste under no-till. This is a long-term experiment, for a period of nine years, where five waste applications were performed: 2002, 2005, 2007, 2009 and 2011. The experimental design was a randomized block with four replications. The treatments consisted of four residues, two municipal wastes (sludge centrifuged and biodigester sludge) and two industrial wastes (blast furnace slag and lime slurry). The dry matter yield and nutrient contents of black oats were determined. The rate of 8 Mg ha(-1) was the only one that showed a significant difference for the dry matter yield from industrial and municipal waste applied. The concentrations of N, P, K and S have not shown any difference as affected of the waste rates. The waste application rates did not affect the levels of Cu and Fe.
Keywords: Avena strigosa; sewage sludge; blast furnace slag; lime slurry; dry matter yield